2022
DOI: 10.1038/s41467-022-31216-4
|View full text |Cite
|
Sign up to set email alerts
|

Healthy cloned offspring derived from freeze-dried somatic cells

Abstract: Maintaining biodiversity is an essential task, but storing germ cells as genetic resources using liquid nitrogen is difficult, expensive, and easily disrupted during disasters. Our aim is to generate cloned mice from freeze-dried somatic cell nuclei, preserved at −30 °C for up to 9 months after freeze drying treatment. All somatic cells died after freeze drying, and nucleic DNA damage significantly increased. However, after nuclear transfer, we produced cloned blastocysts from freeze-dried somatic cells, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Chromosomal analysis showed that the female clone had 39,X karyotype, indicating that the Y chromosome had been lost in the donor cell. The same situation has been observed in clones from ES cells [36], nuclear-transferred ES (ntES) cells derived from freeze-dried fibroblasts [45], and horse SCNT [46]. These findings show that SCNT could be a useful reproductive technique, especially for reviving endangered and extinct species.…”
Section: Selection Of Appropriate Cell Types For Mouse Scntsupporting
confidence: 62%
“…Chromosomal analysis showed that the female clone had 39,X karyotype, indicating that the Y chromosome had been lost in the donor cell. The same situation has been observed in clones from ES cells [36], nuclear-transferred ES (ntES) cells derived from freeze-dried fibroblasts [45], and horse SCNT [46]. These findings show that SCNT could be a useful reproductive technique, especially for reviving endangered and extinct species.…”
Section: Selection Of Appropriate Cell Types For Mouse Scntsupporting
confidence: 62%
“…In our previous study, unidirectional freeze‐drying has been shown to impart large axially aligned microchannels in ANAs, thereby improving their dense internal ultrastructure 30,31 . Notably, the freeze‐drying technique itself can be used as a physical decellularization method, effectively lysing cells within tissues and organs 32,33 . Last, nuclease treatments were carried out to ensure adequate clearance of residual antigenic components within ANAs, allowing them to meet the criteria for in vivo transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the dehydration of somatic cells like lymphocytes or fibroblasts also has helped to make progress in germ cells (Loi et al, 2021; Weng, 2021). The recent birth of healthy cloned offspring derived from freeze‐dried cumulus cells also brings a lot of hope for similar preservation approaches in germ cells (S. Wakayama et al, 2022). Since 2000, sperm cells have been studied in 20 different mammalian species, including humans (Table 1), as ideal candidates for dehydration because of their low water content and compacted DNA.…”
Section: Introductionmentioning
confidence: 99%